Evaluation of a clinical pathway for 'radical laparoscopic prostatectomy': an interrupted time series study. Issue 2 (25th March 2014) - Rotter, Thomas; Machotta, Andreas; Kinsman, Leigh; Champion, Robert
ABSTRACT The aim of this study was a rigorous evaluation of a clinical pathway (CP) in patients who underwent a radical laparoscopic prostatectomy (RLP). The study was performed at a German university hospital. The Department of Urology has considerable expertise and performs more than 200 RLP per year. The CP for 'RLP' was developed based on the best available evidence and introduced in July 2003. It was composed of six modules, and in each module standardized recommendations for clinical examination, therapy and outcome measurement were given. An interrupted time series design with multiple linear regression models was used to measure the effects of a CP for 'RLP' on length of hospital stay, and durations of operation and anaesthesia before and after implementation. χ2 tests were used to compare the number of patients admitted to intensive care unit, the number requiring re‐operation during admission, the number requiring transfusion(s) of blood products and 30‐d readmission rates. A total of 254 patients were analysed. A significant reduction in operation time and admission to intensive care but also a significant increase of patients readmitted to the hospital after the implementation of a CP was observed. Inconclusive results always warrant careful exploration, and measures on CP uptake should always be used to evaluate the success or failure of the implementation strategy.